(untitled) (The Research of Medical Science Review, 2025)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is now the third leading cause of morbidity and mortality worldwide for individuals over 40 years of age. Objective: To evaluate the relationship between Low-Density Lipoprotein to Lymphocyte Ratio (LLR) and the severity of Chronic Obstructive Pulmonary Disease (COPD) and to explore its potential as a biomarker for disease progression. Methods: A cross-sectional study was conducted at the Department of Medicine, King Edward Medical University, Lahore . A total of 284 patients with COPD were enrolled using consecutive non-probability sampling. Data were collected through clinical evaluations, laboratory tests (LDL levels and lymphocyte count), and spirometry. Results: The mean LLR increased significantly with COPD severity (Stage I: 1.12 ± 0.30; Stage II: 1.27 ± 0.32; Stage III: 1.44 ± 0.41; Stage IV: 1.65 ± 0.38; p < 0.001). LLR showed a moderate positive correlation with COPD stages (r = 0.45, p < 0.001). Multivariate regression analysis confirmed LLR as an independent predictor of disease severity (β = 0.38, p < 0.001). ROC curve analysis yielded an AUC of 0.81, with an optimal LLR cutoff of 1.40 (sensitivity: 76.3%, specificity: 78.5%). Conclusion: It is concluded that LLR is a significant and accessible biomarker for assessing COPD severity. Its use in clinical practice could improve early detection and management of severe COPD cases. Further longitudinal studies are recommended to validate these findings and explore the prognostic value of LLR.